Diaphragmatic Thickness Fraction in Subjects at High-Risk for COPD Exacerbations - KARAKURT, SAİT (DAEDALUS ENTERPRISES INC, 2017)
BACKGROUND: Ultrasound-based diaphragmatic thickness fraction is a reflection of the size and function of the diaphragm. This study aimed to examine the value of this measurement in identifying patients with COPD who are at high risk for the development of symptoms and exacerbations. METHODS: This cross-sectional study included 53 subjects with COPD. Respiratory function test results, ultrasonography-based diaphragmatic thickness, symptom scores (modified Medical Research Council dyspnea scale); COPD Assessment Test results, and number of previous exacerbations and admissions were recorded. RESULTS: Only age showed an inverse and weak relation with percent thickness fraction (r = -0.37, P =.006). None of the other variables tested correlated significantly with percent thickness fraction. No association was found between percent thickness fraction and exacerbation frequency, modified Medical Research Council dyspnea scale and COPD Assessment Test symptom scores, or Global Initiative for Chronic Obstructive Lung Disease ABCD risk/symptom assessments. CONCLUSIONS: Diaphragmatic thickness fraction measurements based on diaphragmatic ultrasound assessment in subjects with COPD seemed to be unable to identify subjects at high risk of symptoms and exacerbations as defined by the Global Initiative for Chronic Obstructive Lung Disease ABCD composite disease index.
Keywords: COPD; muscles; respiratory; diaphragm; work of breathing; imaging; radiology; OBSTRUCTIVE PULMONARY-DISEASE; MECHANICAL VENTILATION; ULTRASOUND; DYSPNEA; ULTRASONOGRAPHY; HYPERINFLATION; STRENGTH; VALIDITY; MUSCLES; INDEX